2017
DOI: 10.1016/j.bpj.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tissue Stiffness in Tumors from Mice with Neurofibromatosis-1 Optic Glioma

Abstract: Children with neurofibromatosis type 1 (NF1) cancer predisposition syndrome are prone to the development of low-grade brain tumors (gliomas) within the optic pathway (optic gliomas). One of the key obstacles to developing successful therapeutic strategies for these tumors is the striking lack of information about the mechanical properties that characterize these tumors relative to non-neoplastic optic nerve tissue. To study the physical changes that may occur when an optic nerve glioma is present, we employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Some studies show increased stiffness in glial cell-derived tumors. 1315 In other studies either the shear modulus of glioma tissue was softer than that of normal tissue from the contralateral side 16 or increased stiffening was not observed for the large majority of samples when studied in vivo by ultrasound elastography 17,18 or ex vivo with microindentation 19,20 unless the tissue was compressed. An important finding not generally considered in studies of tumor stiffness is that even when tumor elastic moduli are indistinguishable from those of normal tissue, there is a large difference in viscosity, with gliomas showing less viscous response than adjacent nonmalignant tissue.…”
Section: Introductionmentioning
confidence: 94%
“…Some studies show increased stiffness in glial cell-derived tumors. 1315 In other studies either the shear modulus of glioma tissue was softer than that of normal tissue from the contralateral side 16 or increased stiffening was not observed for the large majority of samples when studied in vivo by ultrasound elastography 17,18 or ex vivo with microindentation 19,20 unless the tissue was compressed. An important finding not generally considered in studies of tumor stiffness is that even when tumor elastic moduli are indistinguishable from those of normal tissue, there is a large difference in viscosity, with gliomas showing less viscous response than adjacent nonmalignant tissue.…”
Section: Introductionmentioning
confidence: 94%
“…However, few reports have demonstrated the expression of MMPs in neurofibromatosis 1. Walter et al showed that increased stiffness of optic nerve tumor may be related to the downregulation of MMP2 in neurofibromatosis 1 29 . In addition, Muir reported that the expression of MMP1 and MMP-9 was increased in cultured cutaneous neurofibroma containing an abundance of Schwann cells 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Cells are sensitive to physical force, and mechanical load on the ECM can expose cryptic ligands [ 24 ]. A stiffer matrix can in and of itself stimulate a cell to undergo an epithelial to mesenchymal transition and begin to migrate [ 25 , 26 ], and there is evidence that the correlation between stiffness and tumour progression also applies in the natural tumour microenvironment [ 27 , 28 ]. Traditional in vitro assays for migration that use a matrix extract or artificial matrix is as a substrate through which cells may or may not migrate may under- or overestimate the invasive potential of some cells that would invade under conditions that might be found in the tumour itself.…”
Section: Cancer Contextmentioning
confidence: 99%